Religious Moderation Education Based on Local Wisdom “Sarakopat” of the Gayo Tribe - Zulkarnain, Zulkarnain; Tamwifi, Irfan; Akbar, Eliyyil (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to describe the importance of building religious moderation education based on local wisdom of Sarakopat. The method used is a case study. The research locus is in Central Aceh Regency which is the center of Gayo culture. Informants were selected purposively, including sarakopat leaders, religious leaders, educators, and community members. Data collection was carried out through in-depth interviews, participatory observation, and documentation studies. The analysis was carried out using the Miles and Huberman interactive model, through the stages of data reduction, presentation, and drawing conclusions. The results of the study indicate that Sarakopat values ​​functionally internalize the principles of religious moderation, such as tolerance, justice, and social empathy. The practical implication is the potential to develop a character education curriculum based on local culture. Theoretically, this study contributes to the study of multicultural education, religious studies, and emphasizes the importance of a local approach in strengthening national values ​​and religious harmony.